Prioritizing implementation factors of electronic document management system (EDMS) using topsis method: A case study in Iraqi government organizations - Abdulkadhim H.; Bahari M.; Hashim H.; Bakri A.; Waidah Ismail (Asian Research Publishing Network, 2024)
Indexed by SCOPUS